A Comparative study in Suppression of Preterm Labor with Nifedipine vs Salbutamol: A Quasi-Experimental study - Jikria, Najmatun; Sayeeda, Nur; Ahmed, Ashiq; Mili, Fahmida Sultana; Salma, Umme (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Background: The primary cause of perinatal morbidity and mortality globally is preterm birth. Obstetricians face a significant challenge in managing preterm labor, while neonatologists face similar difficulties in caring for premature babies. Tocolytic medications are utilized to inhibit premature labor. Salbutamol and Nifedipine have demonstrated the ability to hold preterm labor for a significant and prolongation of period. Objective: To assess the efficacy of nifedipine for supression of preterm labor. Materials and Methods: This comparative quasi-experimental Study was carried out at the Department of Obstetrics and Gynecology, Dhaka Medical College Hospital, Dhaka between October 2019 to September 2021. The study was conducted on 80 patients, where half of them received Nifedipine; half of them received Salbutamol. Results: The study participants were aged between 19-29 years. The mean age of the participants was 23.05 (±2.50) years, and the mean gestational age was 33.8(±1.24) weeks. 80.6% of the participants who received nifedipine can delay preterm labor for 24-48 hours (p<0.05), compared to 46.7% with salbutamol. Considering the complications, nifedipine had lesser complications compared to salbutamol. Palpitation (37.5%) and hypotension (5.0%) occurred with salbutamol. Among them, palpitation (p<0.001) was statistically significant. Conclusion: Nifedipine is a superior tocolytic compared to Salbutamol, as it can prolong pregnancy for a significant period of 24-48 hours. This window provides an opportunity for administering steroids to the patient during labor, which can help reduce the likelihood of respiratory distress syndrome in neonates. Additionally, Nifedipine is associated with fewer side effects, making it one of the best tocolytic medications to be used during pregnancy. Bangladesh J Obstet Gynaecol, 2023; Vol. 38(2): 78-83